2024
DOI: 10.1029/2023jc020175
|View full text |Cite
|
Sign up to set email alerts
|

Interactions Between Internal Solitary Waves and Sea Ice

Samuel G. Hartharn‐Evans,
Magda Carr,
Marek Stastna

Abstract: Internal Solitary Waves (ISWs) that form on internal density interfaces in the ocean are responsible for the horizontal transport and vertical mixing of heat, nutrients, and other water properties. The waves also induce fluid motion that can induce stresses and motion on floating structures, such as sea ice. This study investigates ISW‐sea ice interactions. Using laboratory experiments, ISWs generated via the lock gate technique are observed interacting with weighted floats of varying sizes. The motion of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…A study on the interaction of ISW with an ice sheet by Carr et al (2019) reported that an ice sheet protruding into the pycnocline may cause distortion or even breaking of ISW. Hartharn-Evans et al (2024) investigated the interactions between ISWs and free-floating objects representing sea ice and found that float velocity was dependent on both the amplitude of the wave and the length of the float. At present, there is only a limited number of studies on the interaction between ISWs and ice keels in the laboratory, and previous researchers mainly focused on the motion state of ice, leading to a lack of clarity regarding the characteristics of wave -flow field, and energy of ISWs.…”
mentioning
confidence: 99%
“…A study on the interaction of ISW with an ice sheet by Carr et al (2019) reported that an ice sheet protruding into the pycnocline may cause distortion or even breaking of ISW. Hartharn-Evans et al (2024) investigated the interactions between ISWs and free-floating objects representing sea ice and found that float velocity was dependent on both the amplitude of the wave and the length of the float. At present, there is only a limited number of studies on the interaction between ISWs and ice keels in the laboratory, and previous researchers mainly focused on the motion state of ice, leading to a lack of clarity regarding the characteristics of wave -flow field, and energy of ISWs.…”
mentioning
confidence: 99%